Resistance Strategies of Madurese Moslem Women against Domestic Violence in Rural Society - Fahruddin Ali Sabri; Arif Wahyudi; Fatekhul Mujib (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2020)
Although regarded as weak, helpless and vulnerable for violence, some rural Madurese women are no longer silent and passive in coping with domestic violence they experience. This study aims to identify the survivors’ experiences and choices they made as resistance strategies to reduce or end the violence. The focus was on whether the choices fit with sharia teaching. The study uses empirical legal research and anthropological theory of law and fiqh approach to analyze data. It finds that women who try to take a dispute resolution process show their active attitude and courage to voice injustice, discomfort or disagreement in their domestic life. Some of their strategies fit with shariah teaching while others do not so. However anthropologically, their choice to stop the violence is for the sake of maintaining their marital relation. In the legal sub-culture, they have well considered potential profits and losses as well as the needs or interests they want to get.